Tailored Apodization of Femtosecond Written Fiber Bragg Gratings by Aperture Shaping - Krämer, Ria G.; Schmittner, Christian P.; Goebel, Thorsten A.; Siems, Malte P.; Ullsperger, Tobias; Imogore, Timothy O.; Richter, Daniel; Nolte, Stefan (Optics InfoBase Conference Papers, 2022)
We present the realization of tailored apodization profiles of femtosecond written FBGs using phase mask scanning technique with aperture shaping. By controlling the cross-sectional dimension of the refractive index modification, the spectral response is formed.
CRIS-Team Scopus Importer:2023-04-20